Feasibility study of a coal-fired coupled to biomass power generation technology on a 300 MW unit boiler. (October 2019) - Sun, W; Wang, Y; Liu, G D; Li, Y L
Abstract: This paper describes the characteristics of a coal-fired coupled to biomass power generation technology on a 300 MW unit boiler, the characteristics of the coal-fired coupled to biomass fuel, and the problems and solutions that may occur in the process of coal-fired coupled biomass power generation, as well as the boiler technology transformation plan on the coal-fired coupled to biomass power generation. In terms of study on the characteristics of coal-burning coupled to biomass fuel, the main characteristics of the coal-burning coupled to biomass fuel, such as the combustion characteristics, the ignition characteristics, the burnout characteristics, the slagging characteristics, and the explosion characteristics of the coal-burning coupled to biomass fuel are described. The paper mainly describes the explosion prone problem of the pulverizing system, the pulverized coal hardening problem of the raw coal bunker and the boiler corrosion, and coking problem of the heating surface of the boiler. The explosion-proof transformation of the pulverizing system is described, and the technology transformation of the pulverizing system is carried out. After adopting the technical transformation scheme of sludge, the problems caused by sludge blending and burning are solved, and the power generation by sludge blending and burning is realized.